ESPN Thematic Report on In-work poverty – Finland - Olli Kangas; Laura Kalliomaa-Puha (European Commission, 2022)
Since the international 2008 economic crisis, inequality and poverty in Finland have been in decline. The same goes for in-work poverty (IWP), which in Finland is comparatively low. The Finnish IWP rate was 3.8% in 2012, and 2.7% in 2017. The corresponding figures for the whole EU were 8.9% and 9.6%, respectively. Interestingly enough, there seems to be some divergence between the Finnish and the EU IWP trends. Whereas the EU IWP rates for most population groups seem to have increased slightly, there are downward trends in the Finnish IWP rates measured by gender, age, different household types, intensity of work, employment status and country of origin. This said, it is important to emphasise that the most vulnerable groups exposed to IWP are the same as in the other EU countries: immigrants from non-EU28 or other foreign countries have a larger IWP risk than other groups; the self-employed are more exposed than employees; and low work-intensity households (single mothers, in particular) have higher risks. Therefore, all those policies that directly or indirectly fortify the adult earner model – the model that facilitates both genders in all family situations to fully participate in paid work – are of great importance in reducing IWP.
The low IWP rates in Finland are a result of several underlying factors that are interlinked. First, employees are highly unionised and they can promote their interests via comprehensive collective agreements. The comprehensive social security system increases threshold wages and there are also in-work benefits that mitigate low income caused by low work intensity/low pay. One crucial factor for the low IWP rates has been the prevailing dual-breadwinner and full-time employment model. The full-time employment pattern also effectively prevents IWP. Finally, the share of immigrants (usually employed in low-paid jobs) has been low in Finland.
However, there are several challenges that may change the situation.
·       New forms of contract work and increasing immigration may raise the IWP rates.
·       There are strong demands to diversify wage setting and allow employers to make employment contracts more freely, and to agree upon wages without the interference of the trade unions.
·       On the political agenda there are also voices demanding that the overall role of trade unions must be radically reduced.
·       One big theme on the political agenda is “making work pay”, i.e. eliminating work disincentives, which include, among other policy measures, cutting down social security and making eligibility to benefits more conditional, as well as compelling claimants to accept any jobs, be they short term, part time or low paid. If low incomes from employment are no longer compensated for by social transfers, the IWP rates will inevitably increase.
·       Increasing single parenthood may raise the IWP risk.
·       Maintaining a low degree of IWP requires flexible and diversified income transfers and a wide range of childcare and other family-related services to allow employment and parenthood to be combined.
Our general recommendations are that:
·       When seeking flexibility in the labour market, it is important to have a coordinated bargaining system guaranteeing decent wage levels.
·       Universal care services guarantee the continuation of the defamilised adult earner model, which gives everyone the possibility to fully participate in paid work and effectively prevents in-work poverty.